2014
DOI: 10.18187/pjsor.v10i4.620
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Prediction under a Finite Mixture of Generalized Exponential Lifetime Model

Abstract: In this article a heterogeneous population is represented by a mixture of two generalized exponential distributions. Using the two-sample prediction technique, Bayesian prediction bounds for future order statistics are obtained based on type II censored and complete data. A numerical example is given to illustrate the procedures and the accuracy of the prediction intervals is investigated via extensive Monte Carlo simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To examine the hybrid of two inverse Weibull distributions, Jiang et al 22 focused at the forms of the density and failure rate functions as well as graphical approaches. The following are several authors who deal with mixture modeling in different practical problems: Mohammadi et al, 23 Ateya, 24 Mohamed et al, 25 Sindhu and Aslam, 26 Zhang and Huang, 27 and Sindhu et al [28][29][30][31][32] Some other relevant studies are Ali, 33 Nair and Abdul, 34 and Nassar. 35 Available data in many scenarios can be noticed of as a fusion of two or more models.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the hybrid of two inverse Weibull distributions, Jiang et al 22 focused at the forms of the density and failure rate functions as well as graphical approaches. The following are several authors who deal with mixture modeling in different practical problems: Mohammadi et al, 23 Ateya, 24 Mohamed et al, 25 Sindhu and Aslam, 26 Zhang and Huang, 27 and Sindhu et al [28][29][30][31][32] Some other relevant studies are Ali, 33 Nair and Abdul, 34 and Nassar. 35 Available data in many scenarios can be noticed of as a fusion of two or more models.…”
Section: Introductionmentioning
confidence: 99%
“…Number of researchers has used mixture distributions in a variety of real-world scenarios. [10][11][12][13][14][15] Sindhu et al, [16,17] studied mixture models with industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of MGED over Weibull distribution was explored by Ateya [13], and the industrial applications of MGED were reported by Ali et al [14]. Mohamed et al [15] introduced the methodology to obtain the Bayesian predictions using MGED. Kazmi and Aslam [16] considered the Bayesian analysis for right censored using MGED assuming shape parameters to be known.…”
Section: Introductionmentioning
confidence: 99%